Development of a Rapid Diagnostic Method for Simultaneous Detection of Streptococcus viridans in Cases of Heart Disease - Pestariati Pestariati; Suhariyadi Suhariyadi; Asryadin Asryadin; Nilasari Indah Yuniati (Postgraduate, University of Mataram, 2025)
Heart disease is a leading cause of death worldwide, with a complex pathophysiology often involving interactions between genetic factors, the environment, and pathogenic microorganisms. Streptococcus viridans is a clinically significant pathogenic bacterium associated with infections of the cardiovascular system, including infective endocarditis, pericarditis, and other complications. However, timely and accurate diagnosis of this bacterial infection in cases of acute heart disease is often challenging, requiring rapid and sensitive diagnostic methods. Currently, diagnostic methods for detecting Streptococcus viridans in cases of acute heart disease tend to be time-consuming; therefore, developing a rapid diagnostic method that can detect both bacteria simultaneously is crucial. The aim of this study is to develop a rapid and sensitive diagnostic method for detecting the presence of Streptococcus viridans in samples from patients with heart disease. The method used is the identification of specific genes, the design of primer sequences, and the design of probes using specific 16s rRNA genes using bioinformatics techniques. Based on the research results obtained primer pair sequences are: oligonucleotide primer forward 5’-GCGACGATACATAGCCGAC-3’; primer reverse is 3’- CGAGCCAGTCTGAAAGC-5’, while the probe sequence is 5’-GACTGAGACACGGCCCAGACTC-3’. Primer and probe pair quality tests showed very good primer and probe quality for amplification with a 120 bp amplification product. Suggestions in the research are that it is necessary to continue with qPCR optimization to determine the melting temperature which is then carried out sensitivity tests of primer pair sequences and specific 16s rRNA Streptococcus viridans gene probes.